Impairment of vasomotor reflexes in the fingertips of leprosy patients. Issue 11 (November 1991) - Beck, J S; Abbot, N C; Samson, P D; Butlin, C R; Grange, J M; Cree, I A; Forster, A; Khan, F
Abstract : A method is described for eliciting fingertip vasomotor reflexes by inspiratory gasp and contralateral hand cold challenge. The results of the two tests are reproducible on replicate testing and, when taken together, have proved reliable for detection of impairment of autonomic reflexes in 10 newly registered leprosy patients who did not have any obvious deformity. Similar, but less severe, impairment of vasomotor reflexes was noted in a group of 10 fully treated, apparently cured ex-leprosy patients, none of whom showed clinically obvious neuropathy. Both the new patients and the ex-patients were significantly different from healthy contacts and from healthy Europeans, who were indistinguishable by this test. Evidence is presented suggesting that impairment of these vasomotor reflexes is mainly due to damage to the efferent pathway in the peripheral nerves. The method might prove valuable for investigation of early nerve damage in new patients or during reversal reactions in leprosy at a stage before irreversible damage is done.